Process Evaluation of a Sport-Based Voluntary Medical Male Circumcision Demand-Creation Intervention in Bulawayo, Zimbabwe. (1st October 2016) - DeCelles, Jeff; Hershow, Rebecca B.; Kaufman, Zachary A.; Gannett, Katherine R.; Kombandeya, Thandanani; Chaibva, Cynthia; Ross, David A.; Harrison, Abigail
Abstract : Introduction: Grassroot Soccer (GRS) developed 2 brief and scalable voluntary medical male circumcision (VMMC) promotion interventions for males in Bulawayo, Zimbabwe, consisting of a 60-minute interactive, soccer-themed educational session with follow-up behavioral and logistical reinforcement. Both interventions were led by circumcised male community leaders ("coaches") ages 18–30. "Make The Cut" (MTC) targeted adult males on soccer teams and "Make The Cut+" targeted boys in secondary schools. We conducted a process evaluation of MTC and Make The Cut+ to investigate perceptions of program impact, intervention components, and program delivery; participants' understandings of intervention content; and factors related to uptake. Methods: We conducted 17 interviews and 2 focus group discussions with coaches and 29 interviews with circumcised (n = 13) and uncircumcised participants (n = 16). Results: Findings demonstrate high program acceptability, highlighting the coach–participant relationship as a key factor associated with uptake. Specifically, participants valued the coaches' openness to discuss their personal experiences with VMMC and the accompaniment by their coaches to the VMMC clinic. Conclusions: Should the coach quality remain consistent at scale, MTC offers an effective approach toward generating VMMC demand among males.